2018
DOI: 10.1002/chem.201801543
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Adiabatic Photodehydration of 2‐Hydroxymethylphenol and the Formation of Quinone Methide

Abstract: The photochemical reactivity of 2-hydroxymethylphenol (1) was investigated experimentally by photochemistry under cryogenic conditions, by detecting reactive intermediates by IR spectroscopy, and by using nanosecond and femtosecond transient absorption spectroscopic methods in solution at room temperature. In addition, theoretical studies were performed to facilitate the interpretation of the experimental results and also to simulate the reaction pathway to obtain a better understanding of the reaction mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 105 publications
(180 reference statements)
0
10
0
Order By: Relevance
“…One generally sees very low values for Φ R , which are due to FRET from the naphthol to the naphthalimide. Such a result was not anticipated in the first instance, since it is known that photodehydration takes place in an ultrafast photochemical reaction [ 82 ], which in principle could be in competition with FRET.…”
Section: Resultsmentioning
confidence: 99%
“…One generally sees very low values for Φ R , which are due to FRET from the naphthol to the naphthalimide. Such a result was not anticipated in the first instance, since it is known that photodehydration takes place in an ultrafast photochemical reaction [ 82 ], which in principle could be in competition with FRET.…”
Section: Resultsmentioning
confidence: 99%
“…Benzoxete was also detected by irradiation of a vapor deposition prepared sample of 2- hydroxymethylphenol at 254 nm and 14 K. The characteristic signal at n = 1668 cm -1 (scissoring vibration of the CH2 motif) was clearly observed. 22…”
Section: Ir Spectroscopymentioning
confidence: 99%
“…It was demonstrated that the corresponding QM 2 ( Scheme 1 ) is generated in an ultrafast adiabatic reaction on the S 1 potential energy surface, taking place in less than 1 ps and generating the QM intermediate in its excited S 1 state. 29 However, it is not a general mechanism for the photodehydration, since the formation of QMs may involve benzoxete derivatives as intermediates, 23 or it may proceed via phenoxyl radicals that undergo a homolytic cleavage of the alcohol OH group. 27 …”
Section: Introductionmentioning
confidence: 99%